Pengaruh CEO tenure, feminism in director, dan conservatism terhadap tax avoidance perusahaan properti dan real estate tahun 2021-2023 - Gracia Sherlytta Valensia; Rahma Maulidia; Syarbini Ikhsan (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
Many companies employ strategies to avoid tax liabilities by reducing their tax burden and minimizing their tax liabilities. Weaknesses in tax regulations can be used by these companies to offload their tax liabilities. The purpose of this research is to investigate the impact of factors such as CEO tenure, the existence of women on the board, and the practice of accounting conservatism on tax avoidance. This research investigates companies within the property and real estate sector that are registered on the IDX between 2021-2023. A quantitative approach was employed in this study, utilizing secondary data from company annual reports retrieved from the IDX website and the company's official website. The research adopted purposive sampling for selecting 69 observations. Data processing was carried out using the SPSS 25.0 application. This study found that neither CEO tenure nor the existence of female directors had a significant impact on tax avoidance. However, conservative accounting practices are shown to have a positive and significant impact on tax avoidance. Public interest statements These findings can be utilized by companies in two ways. First, when recruiting leadership, experience or gender diversity alone may not be the strongest indicators to minimize the tax burden. Secondly, the results of this study suggest that tax authorities may need to be more vigilant and selective in their supervision to ensure all taxpayers comply with their tax obligations.